Research in the history of economic thought and methodology. Volume 28A a research annual - Emmett, Ross B.; Biddle, Jeff (Emerald, 2010)
The collection includes both refereed articles and review essays. The articles highlight research on the role of western economic advisors in China before the Communist Revolution (Paul Trescott), John Ryan on minimum wage legislation, a symposium on Clement Juglar, and a comparison of recent work in the history of economics and the history of science. Review essays on new publications examine a range of subjects, including: David Hume's political economy; conceptions of economic morality in American thought; Frank Knight and the Austrians on institutions; Friedrich Engels; Austrian views on entrepreneurship; Coase and Pigou on government intervention; Hayek and conservatism; the history of the "living wage" notion; methodological consideration of economics and econometrics; and Paul Heyne's essays on economic and ethics.